2019
DOI: 10.1111/jai.13912
|View full text |Cite
|
Sign up to set email alerts
|

Fish assemblage in the Pearl River Estuary: Spatial‐seasonal variation, environmental influence and trends over the past three decades

Abstract: The Pearl River Estuary is the largest estuary in South China and plays a considerable role in the local fisheries economy, yet little is known about the current state of fish assemblage in this ecosystem. To quantify spatial‐seasonal variations, environmental influences, and trends over the past three decades of the fish assemblage in the Pearl River Estuary, we sampled 11 sites seasonally from December 2013 to September 2016. Throughout the study, 285 species from 88 families and 195 genera were collected. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 41 publications
0
28
1
Order By: Relevance
“…This high richness and the fish yield from these waters from depths greater than 30 m render this area one of the most important fishing grounds in the SCS (Wang, 2012;Cai et al, 2018). However, fish resources in this region have decreased dramatically in recent decades, largely because of anthropogenic disturbance and climate change (Zeng et al, 2019;Zhou et al, 2019). Meanwhile, the Indo-Pacific humpback dolphin, Sousa Chinese Osbeck, 1765, Indo-Pacific finless porpoise Neophocaena phocaenoides (Cuvier, 1829), Eden's Whale, Balaenoptera edeni Anderson, 1879, Bryde's whale, B. edeni Olsen, 1913, and humpback whale Megaptera novaeangliae Borowski, 1781, which mainly prey on fishes, have all been reported from waters off the Pearl River Estuary (Jefferson et al, 2012;Peilie, 2012;Lin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This high richness and the fish yield from these waters from depths greater than 30 m render this area one of the most important fishing grounds in the SCS (Wang, 2012;Cai et al, 2018). However, fish resources in this region have decreased dramatically in recent decades, largely because of anthropogenic disturbance and climate change (Zeng et al, 2019;Zhou et al, 2019). Meanwhile, the Indo-Pacific humpback dolphin, Sousa Chinese Osbeck, 1765, Indo-Pacific finless porpoise Neophocaena phocaenoides (Cuvier, 1829), Eden's Whale, Balaenoptera edeni Anderson, 1879, Bryde's whale, B. edeni Olsen, 1913, and humpback whale Megaptera novaeangliae Borowski, 1781, which mainly prey on fishes, have all been reported from waters off the Pearl River Estuary (Jefferson et al, 2012;Peilie, 2012;Lin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Estuaries are transition zones between the land and the sea, and represent a dynamic system where freshwater meets seawater. These interactions make estuaries unique habitats in terms of habitat diversity and species productivity (Mitra, 2015;Kamrani et al, 2016;Zhou et al, 2019b). It was previously shown that protective estuary environments may facilitate the generation of over half of all marine fish (Mitra, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It was previously shown that protective estuary environments may facilitate the generation of over half of all marine fish (Mitra, 2015). Moreover, spatial differences in fish assemblages in estuaries were primarily attributed to unique salinity, water temperature, primary productivity, turbidity, and water nutrient conditions (Eick and Thiel, 2014;Zhou et al, 2019b). However, insights on how fish adapt to variable physico-chemical features in these environments requires further investigation (Molina et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of two large European estuaries, Thiel et al., (2003) found that the different life cycle (estuarine use) categories occurred mainly along a spatial gradient with marine and estuarine species arranged in the direction of increasing salinity and decreasing mouth distance, while freshwater species were grouped in the opposite direction. In a study of the fish assemblage of the Pearl River Estuary, China, Zhou et al., (2019) found that the composition of ecological types or estuarine use guilds varied both seasonally and spatially. A longitudinal change was observed which reflected the variable ability of various species to penetrate either fresh or marine waters.…”
Section: Introductionmentioning
confidence: 99%
“…Seasonal change in species richness and estuarine use functional guilds were also observed in relation to the reproduction, recruitment and migration patterns of the various groups of species. Numbers of amphidromous and freshwater species increased in spring with high numbers of marine species occurring in summer (Zhou et al., 2019).…”
Section: Introductionmentioning
confidence: 99%